Formulación del plan de gestión integral de residuos de atención en salud y otras actividades - PGIRASA en la planta de beneficio animal Carnes y Derivados de Occidente S.A. sede Yumbo (2019)
Solid waste and seizures generated in animal welfare plants present a complex environmental and health problem, mainly for the risks they present to public health due to their inappropriate internal management and external. The Ministry of Health and the Ministry of Environment carry out the manual for the integral management of waste generated in health care and other activities - PGIRASA, in order to guide the institutions with the fulfillment of the requirements for the proper management of solid waste. The PGIRASA includes all the aspects to be fulfilled from the generation and segregation in the source, up to the use or final disposal of the waste that reference Decree 351 of 2014 and Title 10 of Decree 780 of 2016. Meats and Derivatives of the West S.A. Yumbo headquarters, is a food company, whose activities generate large and varied amounts of waste solids within the productive process. Currently the company does not have the PGIRASA, causing inconveniences in the handling of waste, for this reason the implementation of a waste management plan will allow the company perform the integral management of the waste generated, obtaining economic and environmental benefits in the process. In the elaboration of the PGIRASA, three stages were carried out together with each one of the items treated in the manual. The diagnosis is the first stage of work, where the recognition of the company and its activities is carried out together with the characterization of waste, yielding qualitative and quantitative results of the management and generation of them in the company. The second stage of analysis allowed to identify the state of the internal management of waste from the results acquired in the first stage, where concludes that 99.68% of the waste generated in the company complies with the adequate use, however, there are aspects to be improved, the segregation in the source and internal storage the most critical in the process. The third stage is the technical proposal of the aspects to be improved compared to the integral management of solid waste, where alternatives are proposed implementation and change in the requirements stated in the manual within of the company. Finally, control of the external management of solid waste is required generated in the company, since it is a requirement of the PGIRASA the follow-up and verification of the proper management of the waste delivered by it